ANALISIS KEBIJAKAN KENAIKAN TARIF PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN PATI MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2009 - Oktavia, Nabila Dina; Afifah Mayaningsih (UIR Law Review, 2025)
This article provides a normative legal analysis of the 2025 policy on increasing the Rural and Urban Land and Building Tax (PBB-P2) rates in Pati Regency, which raised both the tax rate and property value assessment (NJOP) by up to 250%. The policy sparked social protests due to a sharp rise in taxpayers’ bills and concerns over its fairness. Using a normative legal research method with statutory, conceptual, and case approaches, this study examines the legal basis of local government authority, the policy’s conformity with fundamental tax law principles, and its normative implications for taxpayers and local governance. The findings indicate that while the local government’s authority to regulate PBB-P2 is legally valid under Law No. 28 of 2009, the policy substantially contradicts the principles of tax justice, legal certainty, and ability to pay, potentially undermining the legitimacy of local administration. The study recommends greater transparency, public participation, and proportionality in setting PBB-P2 rates to ensure alignment with equitable tax law principles.